وشمية الأيقونة اليهودية بين شماعة الهيمنة و وميض الولادة الجديدة رواية الجنة الثانية لهاني السالمي - فرجاني عبد القادر (University of Eloued جامعة الوادي, 2025)
ملخص تشكل الرواية نموذجا و قالبا فنيا تتجلى فيها التيمات الثقافية المستشفة من تلك الصور التي ترتسم من خلالها العلاقة بين الآنا والآخر ضمن ما يوسم بتمثيلات الصورة التي تشكل هوية الشخصية الناظرة و المنظور إليها مما أدى بكثير من نقاد الرواية إلى أن يستشفوا ثلاث حالات وعي بالآخر ضمن دورة انتقالية ( هوس – رهاب – رمز ) كوضعيات جامعة لتحقق نموذج التسامح من عدمه في ضوء تمثلات الشخصية اليهودية في علاقتها بالشخصيات الأخرى خاصة ضمن بينية تكريس التقاطع وعبثية الحوار ، لتبدو المسألة منوطة بإعادة بنينة الوعي بالشخصية اليهودية في إطار وضعية التسامح في اعتبارها أمرا ثابتا أم استرجاع لمركزيات الآخر في هجومه المضاد على الذات أثناء اشتغاله داخل الجنس الأدبي . Abstract The novel forms a model and artistic template where cultural themes are shown through images depicting the relationship between themselves and the other characterized by the representation of the image that forms the identity of the observation character and perspective from which it is seen. It has inspired many critics of the novel to understand three states of someone else's consciousness in a transitional cycle (passion -phobia - symbol), which is linked to other characters to achieve a model of tolerance or intolerance in the context of Jewish character, especially in the context of communication, tolerant of tolerant of tolerated a literary style, a literary style. Restoration of another centrality in retaliation while working inside.
The Semiotics Of The Jewish Icon : Negotiating Hegemonic Power Dynamics And The Luminescence Of Renewal Hani Al-salmi‘ " The Second Paradies "
مقال.Ex Proffesso.مج 10.. ع. 2
Keywords: التيمات الثقافية ؛ هوس ؛ رهاب ؛رمز ؛التسامح; cultural themes; passion; phobia; symbol; tolerance